2020
DOI: 10.4049/jimmunol.1900912
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effects of Type I and Type III IFNs in the Pathogenesis of Bordetella pertussis Infection and Disease

Abstract: Type I and III IFNs play diverse roles in bacterial infections, being protective for some but deleterious for others. Using RNA-sequencing transcriptomics we investigated lung gene expression responses to Bordetella pertussis infection in adult mice, revealing that type I and III IFN pathways may play an important role in promoting inflammatory responses. In B. pertussisinfected mice, lung type I/III IFN responses correlated with increased proinflammatory cytokine expression and with lung inflammatory patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…5 ). It is known that IFN-位 gene polymorphisms are associated with CMV infections in humans [ 33 ] and recent reports suggest type III IFNs are important for inflammatory responses in Bordetella pertussis infection in mice [ 34 ]. Other than the disease-related pathways, several other critical pathways involved in physiology and pathology like cytokine-cytokine receptor interaction, transcriptional misregulation in cancer, viral protein interaction with cytokine and cytokine receptor, NF-kB signaling pathway, Toll-like receptor (TLR) signaling pathway and others were significantly affected in one or two of the three comparison sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). It is known that IFN-位 gene polymorphisms are associated with CMV infections in humans [ 33 ] and recent reports suggest type III IFNs are important for inflammatory responses in Bordetella pertussis infection in mice [ 34 ]. Other than the disease-related pathways, several other critical pathways involved in physiology and pathology like cytokine-cytokine receptor interaction, transcriptional misregulation in cancer, viral protein interaction with cytokine and cytokine receptor, NF-kB signaling pathway, Toll-like receptor (TLR) signaling pathway and others were significantly affected in one or two of the three comparison sets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is resistant to ubiquitination and degradation because it lacks critical Ser526 phosphorylation of which enables the recruitment of 尾鈥怲rCP E3 ligase 23,24 . Na茂ve Ifnar1 SA mice did not exhibit an overt phenotype, however, they maintained IFNAR1 expression even when challenged with inflammation, 25 viral, 26 or bacterial 27 infection. PMNs鈥怣DSCs from 7鈥恉ay鈥恛ld SA mice expressed markedly higher amount of IFNAR1 than wild鈥恡ype (WT) counterpart (Figure 2(B)).…”
Section: Resultsmentioning
confidence: 99%
“…21,22 PMNs-MDSCs from 7-day-old mice had markedly lower expression of IFNAR1 than PMNs from 14-day-and 6-week-old mice (Figure 2 It is resistant to ubiquitination and degradation because it lacks critical Ser526 phosphorylation of which enables the recruitment of 尾-TrCP E3 ligase. 23,24 Na茂ve Ifnar1 SA mice did not exhibit an overt phenotype, however, they maintained IFNAR1 expression even when challenged with inflammation, 25 viral, 26 or bacterial 27 NEC, the most common gastrointestinal emergency in preterm infants, is a cause for severe neonatal morbidities. It is characterized by ischemic necrosis of the intestinal mucosa, and ensuing severe bowel and systemic inflammation that accompanies the acute intestinal injury.…”
Section: Biologic Role Of Ifn1 In Pmns-mdscs Functionmentioning
confidence: 98%
“…Type I IFN responses can have protective but also detrimental effects during bacterial infections [ 34 , 35 ]. Recent work in IFNAR1-SA mice revealed that increased type I IFN signaling during a B. pertussis infection leads to exacerbated lung pathology in adult mice [ 36 ]. In contrast, this same study showed significantly lower levels of lethality in infant IFNAR1-SA mice infected with B. pertussis as compared to infant wild type mice.…”
Section: Discussionmentioning
confidence: 99%